KKN TEMATIK : PENGAWASAN PARTISIPATIF PADA PEMILIHAN KEPALA DAERAH KABUPATEN SIDOARJO TAHUN 2020 - Endang Wahju Andjariani; Wahyu Rizqi Annisa; Nur Laili Ariani; Rafiqa Nur Alfina (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2021)
The occurrence of various political violations during direct elections that occurred several years earlier in the context of carrying out the democratic process should be used as evaluation material for the implementation of the democratic direct election process party in 2020. This unfair process is very likely to occur if there is no supervision from the surrounding community. Therefore, the role of STKIP PGRI Sidoarjo students is needed by holding a Thematic KKN program in collaboration with the Election Supervisory Board (BAWASLU) in order to create a dignified political climate. The main purpose of this research is to minimize the occurrence of election violations such as money politics, black campaigns in the form of slanderous utterances and fake news thrown by political opponents, mass mobilization by elements of the state civil apparatus at the village level. Supervision in the field of security, order and health is the main focus of this research. The flow of participatory monitoring starts during the quiet period, then continues on the day of voting, until the vote counting process. The forms produced by Participatory Supervision include, 1) Taking precautions with internal or external appeals, 2) Monitoring or supervising directly or indirectly in every campaign activity, 3) Reporting to BAWASLU and or authorized parties. The method used in this research is descriptive qualitative.